Fundamentals of international business - Czinkota, Michael R. (Thomson/South-Western, 2004)
This is an introduction to international business with special emphasis on the environmental and cultural issues facing global organizations. The author team's academic and practitioner experience both in business and government should ensure a balance of research and practical insight.